Using the gene pool of CIMMYT cultivars and lines in spring durum wheat breeding in Western Siberia - V. S. Yusov; М. G. Evdokimov; M. N. Kiriakova; D. A. Glushakov (Труды по прикладной ботанике, генетике и селекции)
Background. Preservation and expansion of the source material genetic diversity and its purposeful use is the basis for the development of adaptable spring durum wheat cultivars for the environments of Western Siberia.Materials and methods. The target research material included the cultivars and promising material of Triticum durum Desf. developed in the Spring Durum Wheat Breeding Laboratory of Omsk Agrarian Scientific Center as well as the gene pool of cultivars and lines obtained under the CIMMYT International Cooperation Program. Field trials, disease resistance assessment and phenological observations were carried out on the experimental fields of the Institute in 2000–2020 according to generally accepted methods. Principal component analysis was carried out using the R version of the 4.0.3 package.Results. The studies have shown that CIMMYT lines differ from local cultivars and lines in disease resistance (brown rust, stem rust, hard smut, and powdery mildew), test weight, pasta-making properties, and lodging resistance, but under the conditions of Western Siberia they are significantly inferior in adaptability to local cultivars and lines and suffer greatly from drought, especially during the grain-filling period. In the genetic control of the studied traits, the additive-dominant system with the inclusion of the complementary recessive epistasis prevails. Local cultivars dominated in most of the studied traits, except the stem length, and the length and diameter of the second internode, where short-stemmed cultivars affected the degree of the traits’ expression in hybrids.Conclusion. The result of such activity was the release of cv. ‘Omsky Korall’, which combines high yield, adaptability to the climate of Western Siberia, and resistance to the local population of Puccinia graminis Pers. f. sp. tritici Erikss. et Henn. and Ug99, with excellent pasta-making properties, as well as the presence of promising lines in all breeding nurseries.